PROSEDUR BRAKHITERAPI INTRAKAVITER HIGH DOSE RATE PADA KANKER SERVIK - Himawan Setyono; Dwi Sugeng Supriyadi; Dria Wanadi (Perhimpunan Radiografer Indonesia (PARI), 2021)
ABSTRACT Background: Radiotherapy hold an important role in cervical cancer treatment. The majority of cervical cancer treatment will be more effective with combination of teletherapy and brachitherapy. In radiotherapy installation facility of Regional General Hospital Dr. Moewardi Surakarta brachitherapy use a high dose rate cobalt 60. The aim of study is to understand cervical cancer intracavity brachitherapy procedure with high dose rate cobalt 60 radiation. Methods: The method of this research was qualitative researchwith case study approachment by observing, interviewing with radiation oncologist doctor, radiotherapy radiographer and medical physicist, and reviewing patient medical record document, simulator image data, treatment planing system resultand patient exposure data. Results: The result of this research showed that cervical cancer brachitherapy procedure in radiotherapy installation facility of Regional General Hospital Dr. Moewardi Surakarta is using one intrauterine applicator, and two ovoid applicator. Applicator position verified by C-arm simulator. Dose calculation is done using TPS GZP 3 and manchester system where point with 2x8.5 Gyor 3x7 Gy. The brachitherapy unit used is GZP 3 Cobalt 60 Afterloading TherapyUnit high dose rate. Conclusions: The reason of using a high dose rate cobalt 60 radiation is to make the time efficient so an optimal result is obtained.